Peran Kepemimpinan Visioner Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam (PAI) di SMP Al-Hasra Depok - Raudoh Fitriah; Eka Naelia Rahmah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
The purpose of this study is to describe the visionary leadership of the principal has a role to help improve the quality of learning in Islamic Religious Education (PAI). This research uses a qualitative research type, as well as a descriptive approach research approach. As the main data source, the headmaster of Al-Hasra Junior High School, Depok. Other supporting sources in the form of books, to obtain data by observation to schools, interviews with school principals, deputy principals in the field of curriculum, Islamic Religious Education (PAI) teachers as well as to five students and students of Depok Al-Hasra Middle School. The results of this study indicate, that the visionary leadership role of school principals in improving the quality of learning in Islamic Religious Education (PAI), namely: The realization of Islamic basic education graduates, encouraging the creation of an atmosphere of learning in accordance with the criteria of quality learning components, supporting the existence of facilities and learning infrastructure, conducting trainings for teachers, adding lessons related to Islamic Religious Education (PAI) learning specifically for Islamic Pekerti Learning (BPI) and supported by religious habituation activities, such as dhuha prayer, guidance of the Qur'an ' the Dzuhur and Asr prayers in congregation, the recitation of students and students held at the home of one of the students and as for the achievements that have been achieved in relation to Islamic Religious Education (PAI) namely Islamic Speech Competition, quiz, MHQ and Adzan at District and Champion level 2 tahfidz juz 30 level Depok City.